Endovascular treatment of the superior mesenteric arteriovenous fistula complicated by gastrointestinal bleeding - Tomasz Jargiełło; Jan Sobstyl; Beata Kasztelan-Szczerbińska; Michał Sojka; Krzysztof Pyra (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Jargiełło T, Sobstyl J, Kasztelan-Szczerbińska B, Sojka M, Pyra K. Endovascular treatment of the superior mesenteric arteriovenous fistula complicated by gastrointestinal bleeding. Turk J Gastroenterol 2019; 30(7): 652-4.